Initial stage of an upflow anaerobic sludge blanket (UASB) reactor start-up - Tan, Yee Ying @ Jennifer; Mohd., Ali Hashim; Kadathur, B. Ramachandran (Penerbit Universiti Sains Malaysia, 2004)
The upflow anaerobic sludge blanket (UASB) process is the most successful new anaerobic reactor design for various industrial and municipal wastewaters (McCarty, 2001). It has become the most popular and widely used high-rate anaerobic wastewater treatment system worldwide (Schmidt and Ahring, 1996, Hulshoff Pol and Lettinga, 1986). Investigated and developed by Lettinga and his team since 1971 (Lettinga et. al., 1980), it was one of the anaerobic treatment systems that answered the urgent need for alternative treatment systems in view of increased environmental concerns amidst the energy crisis in the 1970s.